PDMS and DLC‐coated unidirectional valves for artificial urinary sphincters: Opening performance after 126 days of immersion in urine. Issue 4 (2nd November 2021) - Mazzocchi, Tommaso; Lucarini, Gioia; Roehrer, Irene; Menciassi, Arianna; Ricotti, Leonardo
Abstract: In this work, unidirectional valves made of bare polydimethylsiloxane (PDMS) and PDMS provided with a micrometric diamond‐like carbon (DLC) coating were fabricated and characterized, in terms of surface properties and opening pressure. The valve performance was also tested over 1250 repeated cycles of opening/closure in water, finding a slight decrease in the opening pressure after such cycles (10%) for the PDMS valves, while almost no variation for the PDMS + DLC ones. The valves were then immersed in urine for 126 days, evaluating the formation of encrustations and the trend of the opening pressure over time. Results showed that PDMS valves were featured by a thin layer of encrustations after 126 days, but the overall encrustation level was much smaller than the one shown by PDMS in static conditions. Furthermore, the opening pressure was almost not affected by such a thin layer of crystals. DLC‐coated valves showed even less encrustations at the same time‐point, with no significant loss of performance over time, although they were featured by a higher variability. These results suggest that most encrustations can be removed by the mechanical action of the valve during daily openings/closures. Such a self‐cleaning behavior with respect to a static condition opens exciting scenarios for the long‐term functionality of mobile devices operating in the urinary environment.